Bad news ... Or maybe not! - Macedo, António (2009)
Are these really bad news (A CASE REPORT OF TUBERCULOUS LYMPHADENITIS) Introduction: Peripheral lymphadenopathy constitutes a diagnostic problem to the family physician. The following case pretends to demonstrate and discuss the approach to cervical lymphadenopathy in primary care, the importance of clinical history and physical examination and of the coordination with secondary care. Case description:Woman, 43 years old, unemployed, divorced and with two children, with prior history of allergic rhinitis, sinusitis, varicetomy and depression, and a family history of pulmonary tuberculosis in first degree relatives. She seeks her primary care provider with a painful tumefaction in the posterior triangle of the neck with one year of evolution. An ecographic study shows an adenomegaly and the suspicion of Hodgkin's disease.The patient is referred to secondary care where she is submitted to an exsicional biopsy.After histologic analysis and culture in specific medium a diagnosis of tuberculous lymphadenitis is reached. The patient was then oriented to a tuberculosis clinic for treatment. Comentary: This case reveals the importance of a systematic evaluation of lymphadenopathy in the differential diagnosis and tuberculosis as a prevalent problem in Portugal for wich the family physician must be alerted to. It is demonstrated the relevance of the family doctor as a cornerstone of the health care system as the first and constant link to the different levels of health care provision.